Foraging Niche Separation of Adélie (Pygoscelis adeliae) and Gentoo (P. papua) Penguins During the Breeding Season at Palmer Station, Antarctica - Pickett, Erin
Climate-induced range overlap can result in novel interactions between similar species and potentially lead to competitive exclusion. The Western Antarctic Peninsula is one of the most rapidly warming regions on Earth and is experiencing a poleward climate migration. This transition from a polar to sub-polar environment has resulted in a range expansion of the ice-intolerant gentoo penguin (Pygoscelis papua) and a coincident decline of ice-obligate Adélie penguins (P. adeliae) at Palmer Station, Anvers Island (64˚46’S, 64˚03’W). Ecologically similar species that share a limited prey resource must occupy disparate foraging niches in order to co-exist. Therefore, the aim of this study was to determine the extent of spatial and dietary niche segregation between Adélie and gentoo penguins during the breeding season at Palmer Station. This research was conducted across six austral breeding seasons, from 2010-2015, which allowed for an investigation of the consistency of niche overlap in the context of resource variability. This study was conducted using a twofold methodological approach involving biotelemetry and diet sampling, and little evidence was found to suggest that foraging competition is a primary driver of penguin population trajectories in this region. While substantial overlap was observed in the diets of Adélie and gentoo penguins, who consumed primarily Antarctic krill (Euphausia superba), these results show that Adélie and gentoo penguins partitioned this shared prey resource through horizontal and vertical segregation of their core foraging areas. No evidence was found to suggest that Antarctic krill is a limiting resource during the breeding season or that climate-induced sympatry of Adélie and gentoo penguins has resulted in competition for prey and the subsequent differing population trajectories. Rather, other physical and biological changes to the ecosystem due to the rapidly changing climate around the Antarctic Peninsula may have stronger influences on the current trends of these two species in ...